Starejše rokopisne pesmarice vzhodnoslovenskega prostora - Ditmajer, Nina (University of Maribor Press, 2024)
Today’s Eastern Slovenia comprises the geographical area of Eastern Styria between the Drava and Mura rivers, where the inhabitants speak the Prleško and Slovenian Goričko dialects, as well as the area of Prekmurje, which extends to the present-day border with Hungary. In the past, this area was part of a larger linguistic and literary system that began to take shape in the Middle Ages with the establishment of the East Frankish border county of Lower Pannonia, which included the area between the Danube and the Sava basin. At the end of the 11th century, the territory of Prekmurje came under the legal authority of Hungary, and the ecclesiastical administration was placed under the Dioceses of Zagreb and Györ (from 1777 to St Gotthard). Only after the collapse of Austria-Hungary in 1919 did it become part of today’s Slovenian territory, with the exception of the area along the Upper Raba River and the area around Monošter. The people of Prekmurje have cultivated their own literature, which was significantly influenced by the Kaikavian, Burgenland and Hungarian literary traditions, since the 16th century. The literary language was established in Küzmich’s translation of the New Testament (1771), while authors from Prekmurje established it from the mid-19th century in all functional genres of the language. The first printed books of Prekmurje Slovenians known today are the Catechismus and the Abecedarium (1715, 1725). Nevertheless, the existence of numerous manuscripts, especially hymnbooks, proves the continuous use of the literary language of Prekmurje at least from the 16th century until the First World War, when Protestant writers adopted the common Slovenian literary norm...